PELATIHAN BAHASA INGGRIS UNTUK PELAKU WISATA DALAM MENDUKUNG PARIWISATA DI DESA AEK GALOGA: PELATIHAN BAHASA INGGRIS UNTUK PELAKU WISATA DALAM MENDUKUNG PARIWISATA DI DESA AEK GALOGA - Shoufi Nisma Dewi; Novria Grahmayanuri; Riskiana aritonang, Devinna (CV. Alfa Pustaka, 2024)
English training for tourism actors aims to improve communication competency in supporting tourism development in Aek Galoga Village, which has great potential as a leading tourist destination. This article describes the stages of training implementation, the results obtained, and its impact on the communication skills of local tourism actors. The training was conducted through a direct practice-based approach, including conversation simulations. The results showed a significant increase in participants' communication skills. This program is the first step towards more professional community-based tourism management.